2015
DOI: 10.1542/hpeds.2014-0168
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Plans for Those Selecting Hospital Medicine as an Initial Career Choice

Abstract: BACKGROUND: The proportion of the newly graduated pediatric workforce that becomes hospitalists has been increasing slightly over the past decade. However, it is unknown what proportion of those who accept hospitalist positions as their fi rst job intend to remain in the fi eld longer term. This is important to workforce projections regarding the magnitude of those who will function in this role. METHODS:The American Board of Pediatrics incorporated a structured questionnaire within the online application proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…Results of a previously published ABP survey reported that 8% of residents planned to work as hospitalists following residency, with 43% of these envisioning long-term hospitalist careers. 12 These differences may reflect different sampling strategies and survey timing; our survey was administered during or following residents' last month of training, while the ABP survey was conducted earlier during the academic year.…”
Section: Discussionmentioning
confidence: 99%
“…Results of a previously published ABP survey reported that 8% of residents planned to work as hospitalists following residency, with 43% of these envisioning long-term hospitalist careers. 12 These differences may reflect different sampling strategies and survey timing; our survey was administered during or following residents' last month of training, while the ABP survey was conducted earlier during the academic year.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 More recently, 8% of pediatric residents reported PHM as their chosen area of practice upon completion of residency, with half of these intending PHM to be their long-term career path. 4,5 Thus, PHM represents one of the largest areas of practice for graduating pediatric residents.…”
Section: Development and Growth Of Pediatric Hospital Medicinementioning
confidence: 99%
“…Ultimately, the study's fi nding that less than one-half of those taking a PHM job are planning a career in PHM is diffi cult to interpret, given the mixed group of respondents and the lack of clarity regarding the nature of the PHM position they are assuming. Other studies, including a recent American Academy of Pediatrics survey, indicate a higher percentage of retention and more maturity of the PHM workforce than implied by the study of Freed et al 1 Perhaps the most interesting results were those of the respondents who identifi ed themselves as advancing to fellowship training on the way to a career in PHM. This group is analogous to those entering other ABP-certifi ed fellowship programs.…”
mentioning
confidence: 88%